4(5x+2)=4(3x+2)

Simple and best practice solution for 4(5x+2)=4(3x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5x+2)=4(3x+2) equation:


Simplifying
4(5x + 2) = 4(3x + 2)

Reorder the terms:
4(2 + 5x) = 4(3x + 2)
(2 * 4 + 5x * 4) = 4(3x + 2)
(8 + 20x) = 4(3x + 2)

Reorder the terms:
8 + 20x = 4(2 + 3x)
8 + 20x = (2 * 4 + 3x * 4)
8 + 20x = (8 + 12x)

Add '-8' to each side of the equation.
8 + -8 + 20x = 8 + -8 + 12x

Combine like terms: 8 + -8 = 0
0 + 20x = 8 + -8 + 12x
20x = 8 + -8 + 12x

Combine like terms: 8 + -8 = 0
20x = 0 + 12x
20x = 12x

Solving
20x = 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
20x + -12x = 12x + -12x

Combine like terms: 20x + -12x = 8x
8x = 12x + -12x

Combine like terms: 12x + -12x = 0
8x = 0

Divide each side by '8'.
x = 0

Simplifying
x = 0

See similar equations:

| (12x-7)+(13-4x)= | | y=26+4x | | p-3(p-1)=2+(2p+5) | | -5c=-25 | | (3+i)(6-2i)= | | 4v-4=-8 | | 45x-12=80 | | N-6.5=15 | | x^2+32x+130=0 | | 3x^2+6x^2y-9x^2z= | | (2x-7)(x+4)=33856 | | -14n=42 | | 2x+5+7x+8x=107 | | 1/5w-4=-2 | | -2nb=-6z | | 25=-4c+97 | | 4(y-6)+14(y+10)= | | -a-2a=-24 | | K-17.8=-3 | | 6d=78 | | -17p=0102 | | 15-=y/7 | | x+(x+-38)=180 | | -2(r+4)=24 | | 3(a-4)+15=13 | | 12p=15 | | 4(x-6)+14(x+10)= | | 129=15 | | 240=(5*w*2)+(w*2) | | 89=0.9d+71 | | 408b=36 | | (3/10)*(5/3) |

Equations solver categories